Personal life satisfaction as a measure of societal happiness is an individualistic presumption: evidence from fifty countries - Kuba, K. (2021)
Numerous studies document that societal happiness is correlated with individualism, but the nature of this phenomenon remains understudied. In the current paper, we address this gap and test the reasoning that individualism correlates with societal happiness because the most common measure of societal happiness (i.e., country-level aggregates of personal life satisfaction) is individualism-themed. With the data collected from 13,009 participants across fifty countries, we compare associations of four types of happiness (out of which three are more collectivism-themed than personal life satisfaction) with two different measures of individualism. We replicated previous findings by demonstrating that societal happiness measured as country-level aggregate of personal life satisfaction is correlated with individualism. Importantly though, we also found that the country-level aggregates of the collectivism-themed measures of happiness do not tend to be significantly correlated with individualism. Implications for happiness studies and for policy makers are signaled.